Sexual Assault Of Females: The Role of Television in Shaping Sexual Behaviour of Youth - Ekwenchi, Ogochukwu Charity; Onwuagba, Maryrose Ifeyinwa (Social Science Research, 2024)
The need to identify strategies in improving television media programming and promotion of nudity, hard drug consumption and aggressive sexual content via movies, musicals and advertisement in this Age of Yahoo Plus, Mkpurummiri and Oke Ite driven society is germane. This was as a result of increase in cases of sexual assault of female gender –Minor, adolescent, adult and elderly seen as obscene and depredation on media practitioners in global perspective. This study has shown that sexual content prevalent in television programming and movies with drug –addicted themes have deleterious effect on viewer’s attitudes about sex, The researchers investigated: What is responsible for upsurge of rape in this age? What makes men to sexually assault the female gender? How do male gender viewing TV models addicted to Mkpurummiri behave in sexual relationship with females? Whether there is relationship between youths’ exposure to violent television sexual content and aggressive attitudes in sexual relationship within the theoretical framework of Cultivation theory. Qualitative research design via FGD of 70 respondents purposely drawn from National Association of Women Journalists (NAWOJ) Delta state was used to collect data for the study. Data analysis and interpretation was done using Rubin and Rubin thematic stance. Result shows that high consumption of hard drugs, idleness, pornographic series, prolonged strike and alcoholic beverages are major factors for upsurge of rape and males addicted to Mkpurummiri reacts violently to females in sexual relationship. The study finds significant relationship between youths’ exposure to violent television sexual themes and aggressive attitudes in sexual relationship within the theoretical framework of Cultivation theory. Respondents recommended Weekly Family Drug-Rape Preventive Dialogue (WFD-RPD) at home, School Monthly Drug-Rape Preventive Dialogue (SMD-RPD). The paper posit that descent television programming imparting morality and respect for female genders’ sexuality could be used to minimize rape and drug addiction for a better, happier and safer world.